[LB.03.03] SYMPATHETIC NERVE ACTIVITY IS INDEPENDENTLY LINKED TO GEOMETRIC AND ELASTIC PROPERTIES OF COMMON CAROTID ARTERY IN RESISTANT HYPERTENSION. (September 2017) - Hering, D.; Nowak, R.; Czechowicz, K.; Kucharska, W.; Boutouyrie, P.; Laurent, S.; Narkiewicz, K.
Abstract : Objective: Patients with resistant hypertension (RH) are characterized by high levels of muscle sympathetic nerve activity (MSNA). However, the underlying pathophysiological mechanisms are not entirely understood. The relationship between direct measures of MSNA and common carotid artery (CCA) properties in RH has not yet been investigated. This study aimed to determine whether sympathetic nerve activity is independently linked to geometric and elastic properties of CCA. Design and method: We measured MSNA (microneurography), heart rate (ECG), arterial pressure (Finapres system), CCA intima-media thickness (IMT), steady and pulsatile carotid circumferential wall stress (CWS), and distensibility (ArtLab system) in 15 patients with true RH (age 55 ± 1 years, BMI 33 ± 1 kg/m 2, mean ± SEM) confirmed by ambulatory daytime systolic (S) and diastolic (D) blood pressure (BP) (161 ± 3/94 ± 4 mmHg). Results: MSNA averaged 57 ± 2 bursts/min., mean CCA intima-media thickness 0.79 ± 0.04 mm, stroke change in diameter 699 ± 193 μm, carotid distensibility 21 ± 2 kPa −1 10 −3, systolic (s) CWS 93 ± 5 kPa, diatolic (d) CWS 56 ± 3 kPa, mean (m) CWS 74 ± 4 kPa and pulsatile (p) CWS 36 ± 2 kPa. CCA IMT was inversely related to MSNA (r = −0.54, P < 0.05) and sCWS (r = −0.74, P < 0.001), dCWS (r = −0.88, P < 0.001), mCWS (r = −0.82, P < 0.001), but not pCWS (r = −0.37, P = 0.18). Baseline resting MSNA was significantly associated with sCWS (r = 0.52, P < 0.05), dCWS (r = 0.56, P < 0.05), mCWS (r = 0.52, P < 0.05), but neither to pCWS (r = 0.30, P = 0.28) nor distensibility (r = −0.09, P = 0.74). The relationship between MSNA and CCA IMT, and CWS remained significant after adjustment for age, BMI, SBP, DBP and heart rate. Conclusions: The relationship between augmented sympathetic activation and higher carotid wall stress in patients with RH suggests the desensitization of carotid arterial baroreflexes in response to cyclic increases in BP. The low intima-media-thickening in the presence of both elevated BP and sympathetic activation indicates an inappropriate arterial remodeling in RH, leading to high CWS, thereby further potentiating cardiovascular risk in this patient cohort.